Determinação de toxicidade cianogênica e carboidratos solúveis totais em cultivares de mandioca (Manihot esculenta Crantz) - de Battisti, Cremilda Rosa; Franco Feitosa Teles, Francisco; Teixeira Coelho, Dilson; da Silveira, Américo José; Martins Batista, Cid (Revista Ceres, 2025)
The total soluble carbohydrates (CST) and the HCN content were determined for ten cassava cultivars grown in the state of Minas Gerais.